Acute Flaccid Paralysis with Acute Encephalitis Syndrome at a tertiary care centre of eastern Nepal - Chaudhary, Shipra; Singh, Rupa Rajbhandari; Bhatta, Nisha Keshary; Shah, Gauri Shankar; Agrawal, Jyoti (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Acute encephalitis syndrome (AES) can have widely varied presentation. Hence this study was done to find out clinical features and outcome of Acute Enecphalitis Syndrome (AES) with Acute Flaccid Paralysis (AFP). Materials & Methods: A Prospective hospital-based study was carried out over one-year period, including all cases fulfilling AFP case definition. All cases of AFP meeting AES definition were further analysed in terms of history, clinical examination, investigations and outcome. Statistical analysis was done using SPSS version 17. Results: Out of total 43 children with AFP, 23 (53.5%) children had AES. Amongst AFP with AES, altered mental status and seizures were present in 87% and 74% respectively. The mean Glasgow Coma Scale (GCS) was 7.61±3.65. Predominant weakness pattern was quadriparesis (87%). Cerebrospinal fluid was abnormal in 11 (47.9%) children with Japanese encephalitis (JE) positive 8.7%. Amongst 60.9% children with complications, respiratory failure (52.1%) was the most common. During 60-day follow-up, 11 (47.9%) children expired while 2 (8.7%) still had residual paralysis. Conclusion: AES is one of the common causes of AFP besides other causes. AFP with AES is commonly associated with quadriparesis, low GCS, respiratory complications, neurological sequelae and a high mortality. Thus, this study stresses upon the importance of AES surveillance along with AFP surveillance.